THE EFFECT OF INQUIRY-BASED LEARNING METHOD ON SENIOR HIGH SCHOOL STUDENT’S CONCEPTUAL UNDERSTANDING OF HEAT AND SCIENTIFIC PROCESS SKILLS - Solikin Solikin; Nurdin Bukit; Derlina Derlina (Jurnal Pendidikan Fisika, 2020)
This study aims to analyze the differences: (1) the conceptual understanding of students taught with inquiry-based learning method and conventional learning, (2) the scientific process skills of students taught with inquiry-based learning method and conventional one. This research employed a quasi experimental method. The population of study was XI grade student of SMA Al Fityan Medan. The sample was chosen randomly. The instrument used in this research were multiple choice questions and observation sheet. multiple choice questions were used to analyzed student’s conceptual understanding, while observation sheet were used to investigate student’s scientific process skills. The data of this research were analyzed using independent sample  t-test. the results of this study showed a significant difference, that can be conclude as bellow: (1) the conceptual understanding of students taught with inquiry-based learning method are better than the students taught with conventional learning, (2) the scientific process skills of students taught with inquiry-based learning method are better than the students taught with conventional learning